2017
DOI: 10.1186/s13024-017-0175-y
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-derived IL-1β promotes chemokine expression by Müller cells and RPE in focal retinal degeneration

Abstract: BackgroundChemokine signalling is required for the homing of leukocytes during retinal inflammation, and is associated with pathogenesis of diseases such as age-related macular degeneration (AMD). Here, we explore the role of interleukin-1β (IL-1β) in modulating AMD-associated chemokines Ccl2, Cxcl1, and Cxcl10 during photo-oxidative retinal damage, and the effect on both the accumulation of outer-retinal macrophages, and death of photoreceptors.MethodsInhibition of retinal IL-1β expression was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 47 publications
5
92
0
Order By: Relevance
“…These findings were replicated by Natoli et al. () in rat retina model underscoring their importance in vivo as well. CCL2/MCP‐1 facilitates the migration and infiltration of circulating monocytes that play a key role for CNV formation upon retinal stress (Kersten et al.…”
Section: Discussionmentioning
confidence: 52%
“…These findings were replicated by Natoli et al. () in rat retina model underscoring their importance in vivo as well. CCL2/MCP‐1 facilitates the migration and infiltration of circulating monocytes that play a key role for CNV formation upon retinal stress (Kersten et al.…”
Section: Discussionmentioning
confidence: 52%
“…Activated microglia are heavily involved in diabetes and retinal degeneration (Natoli et al, ). In our study, microglia were identified by Iba‐1 immunolabelling and showed the characteristics of activated microglia with hypertrophied cell body in STZ‐diabetic retina unlike microglia in control rats displaying small size cytoplasm, in agreement with previous studies (Zeng et al, ; Krady et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these morphological changes, activated microglia can acquire an altered gene expression pattern toward functionally distinct phenotypes. Once provoked, microglia produce pro‐inflammatory cytokines and chemokines, such as IL‐1, IL‐6, IL‐23, interferon gamma‐γ (IFN‐γ), CC chemokine ligand 2 (CCL2) and tumor necrosis factor‐α (TNF‐α) (Natoli et al, ; Nicolas et al, ; Smith, Das, Ray, & Banik, ), which are toxic to neighboring neurons and other glial cells such as astrocytes and oligodendrocytes. Nevertheless, activated microglia are more than simply destructive, it being widely recognized that immunoregulatory microglia are required for regulating brain repair and regeneration by secreting anti‐inflammatory factors, such as IL‐4, IL‐10, IL‐13, and TGF‐β (Cherry, Olschowka, & O'Banion, ; X. Jin & Yamashita, ).…”
Section: The Role Of Microglia In Neurological Diseases: Friend or Foe?mentioning
confidence: 99%